Distinct HIV Type 1 Strains in Different Risk Groups and the Absence of New Infections by Drug-Resistant Strains in Lithuania - Caplinskas, Saulius (Mary Ann Liebert, Inc., 2013)
To analyze HIV-1 genotypes in Lithuania and the transmission of drug-resistant viruses, HIV-1 sequences were obtained from 138 individuals, who were diagnosed as HIV-1 infected in 1990–2008 and represented all major risk groups. Subtype A strains, dominating in the former Soviet Union (90% of cases), were found in 60% of individuals, followed by subtype B (22%) and CRF03_AB (12%) strains. The remaining 7% of the strains included variants belonging to subtype C, CRF01_AE, CRF02_AG, more complex recombinant forms, and strains that could not be reliably genotyped. Analysis of virus genotypes per risk group revealed the circulation of distinct HIV-1 strains in different risk groups: subtype A viruses were present in 82% of injecting drug users (IDUs), but less than a half of heterosexually infected individuals and cases with unknown transmission route, and none of men having sex with men (MSM). We observed no mutations causing drug resistance among 27 newly diagnosed HIV-1 cases.